Organizational Innovation, Capacities, Services and Creativity in technology-based companies. Case Study on Technology-Based Service Companies in a Developing Country (LACCEI, 2024)
Abstract– The objective of this research is to analyze the relationship between the company's organizational innovation, the company's innovation capacity process, product innovation and the creativity of employees in a Tech based company in the Dominican Republic. A quantitative methodology was used, based on the application of a validated survey. The data were analyzed with the SPSS and PLS programs. The results show a positive influence of organizational innovation on the company's innovation capacity process, as well as on product innovation and creativity. Keywords-- innovation, process, service, creativity, business